Communicating women’s health: Social and cultural norms that influence health decisions - Gatison, A.M. (Taylor and Francis, 2015)
This volume explores the conditions under which women are empowered, and feel entitled, to make the health decisions that are best for them. At its core, it illuminates how the most basic element of communication, voice, has been summarily suppressed for entire groups of women when it comes to control of their own sexuality, reproductive lives, and health. By giving voice to these women’s experiences, the book shines a light on ways to improve health communication for women. Bringing together personal narratives, key theory and literature, and original qualitative and quantitative studies, the book provides an in-depth comparative picture of how and why women’s health varies for distinct groups of women. Organized into four parts-historical influences on patient and provider perceptions, breast cancer the silence and the shame, make it taboo: mothering, reproduction, and womanhood, and sex, sexuality, relational health, and womanhood-each section is introduced with a brief synthesis and discussion of the key questions addressed across the chapters. © 2016 Taylor & Francis.
Journal Abbreviation: Communicating Women’s Health: Social and Cultural Norms that Influence Health Decisions Pages: 199 Publication Title: Communicating Women’s Health: Social and Cultural Norms that Influence Health Decisions
Keywords: dept.com